Stress and Burnout in Health-Care Workers after the 2009 L’Aquila Earthquake: A Cross-Sectional Observational Study - Mattei, Antonella; Fiasca, Fabiana; Mazzei, Mariachiara; Necozione, Stefano; Bianchini, Valeria (Frontiers in Psychiatry, 2017)
Burnout is a work-related mental health impairment, which is now recognized as a real problem in the context of the helping professions due to its adverse health outcomes on efficiency. To our knowledge, the literature on the post-disaster scenario in Italy is limited by a focus on mental health professionals rather than other health care workers. Our cross-sectional study aims to evaluate the prevalence of burnout and psychopathological distress in different categories of health care workers, i.e., physicians, nurses and health care assistants, working in different departments of L’Aquila St. Salvatore General Hospital six years after the 2009 earthquake in order to prevent and reduce work-related burnout. With a two-stage cluster sampling, a total of 8 departments out of a total of 28 departments were selected and the total sample included 300 health care workers. All the participants completed the following self-reporting questionnaires: a socio-demographic data form, an MBI and a GHQ-12. Statistically significant differences emerged between the total scores of the GHQ-12: posthoc analysis showed that the total average scores of the GHQ-12 were significantly higher in doctors than in health care assistants. A high prevalence of burnout among doctors (25.97%) emerged. Using multivariate analysis, we identified a hostile relationship with colleagues, direct exposure to the L’Aquila earthquake and moderate to high levels of distress as being burnout predictors. Investigating the prevalence of burnout and distress in health care staff in a post-disaster setting and identifying predictors of burnout development such as stress levels, time-management skills and work-life balance will contribute to the development of preventative strategies and better organization at work with a view to improving public health efficacy and reducing public health costs, given that these workers live in the disaster-affected community as survivors and serve as disaster relief workers at the same time.